Fabrication and photoelectrochemical properties of TiO2/CuInS2/Bi2S3 core/shell/shell nanorods electrodes. Issue 96 (17th October 2015) - Wan, Yanling; Han, Minmin; Yu, Limin; Jia, Junhong; Yi, Gewen
<x xml:space="preserve">Abstract</x> The FESEM images (a and b), photocurrent density versus potential (c–v) curves (c) and schematic of the energy level arrangement (d).